2021
DOI: 10.1038/s41598-021-85978-w
|View full text |Cite
|
Sign up to set email alerts
|

Dolomite genesis in bioturbated marine zones of an early-middle Miocene coastal mud volcano outcrop (Kuwait)

Abstract: The origin of spheroidal dolomitized burrow from Al-Subiya sabkha in Kuwait was previously described as enigmatic as no evidence of precursor calcium carbonate was found in the siliciclastic sediment. An assumption for the genesis of spheroidal dolomite from the same area was attributed to hydrocarbon seepage but no evidence was provided. Here, we investigated a recently discovered early-middle Miocene coastal mud volcano outcrop in Al-Subiya sabkha where dolomitized burrows and spheroidal dolomite are found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…In reported cases of burrow‐selective dolomitization during periods with low seawater Mg/Ca ratios, depositional environments are the restricted lagoon or tidal flat settings with high seawater salinity and sufficient Mg supply. Additionally, host rocks in these environments are primarily composed of lime mudstone or wackestone causing the permeability superiority of burrows over surrounding matrices, which contributes to the preferential fluid flux and dolomitization within burrows (Morrow, 1978; Saller & Yaremko, 1994; Rameil, 2008; Baniak et al ., 2014; Newport et al ., 2020; Rahim et al ., 2020; Alibrahim et al ., 2021; Ye et al ., 2021; Yang et al ., 2022a). By contrast, the Rumaila Formation was deposited in an open marine with normal seawater salinity and the host rocks were dominantly packstone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reported cases of burrow‐selective dolomitization during periods with low seawater Mg/Ca ratios, depositional environments are the restricted lagoon or tidal flat settings with high seawater salinity and sufficient Mg supply. Additionally, host rocks in these environments are primarily composed of lime mudstone or wackestone causing the permeability superiority of burrows over surrounding matrices, which contributes to the preferential fluid flux and dolomitization within burrows (Morrow, 1978; Saller & Yaremko, 1994; Rameil, 2008; Baniak et al ., 2014; Newport et al ., 2020; Rahim et al ., 2020; Alibrahim et al ., 2021; Ye et al ., 2021; Yang et al ., 2022a). By contrast, the Rumaila Formation was deposited in an open marine with normal seawater salinity and the host rocks were dominantly packstone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Mg produced by burrow organisms and supplied by coeval seawater (Gingras et al ., 2004b; Rameil, 2008; Chatalov, 2018), several additional Mg sources and pump mechanisms have been proposed. The most prevalent source is dense saltwater with a high Mg concentration, pumped by shallow seepage reflux and/or evaporitic tidal pumping (Morrow, 1978; Saller & Yaremko, 1994; Zenger, 1996a; Baniak et al ., 2014; Baldermann et al ., 2015; Niu et al ., 2020; Rahim et al ., 2020; Alibrahim et al ., 2021; Ye et al ., 2021; Yang et al ., 2022a). Moreover, Callen & Herrmann (2019) found that the leaching of volcanic ash could provide Mg for burrow dolomitization.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent investigation, the geochemical signatures of dolomite were characterized, indicating strictly anoxic conditions that imply methane seepage during the Miocene period. Under such conditions, dolomite formation was suggested to be prompted by microbial consortia associated with the anaerobic oxidation of methane [47]. Despite the significance of these findings, the involvement of microbes in dolomite formation in Al-Subiya area was postulated but not verified.…”
Section: Introductionmentioning
confidence: 92%
“…The observed pockmarks indicate intense venting of hydrocarbon-charged fluids where the authigenic carbonates are consequences of the microbial anaerobic oxidation of seeped hydrocarbon. The geochemical signatures of positive cerium and europium anomalies of dolomite at the site provide strong evidence of strictly anoxic conditions and sulfate reduction events during the dolomite formation process [47]. Prior to rock sampling for our research, the site was divided into 3 zones based on apparent lithological and geomorphological characteristics (Figure 1).…”
Section: Sample Materialsmentioning
confidence: 99%
“…So far, massive dolostones are attributed to slow burial or hydrothermal dolomitization of calcite or aragonite precursors by Mg-rich fluids at temperatures of >100 °C [3,5,6]. In contrast, other studies have asserted that dolomites can form at low temperatures in pore waters during early diagenesis [7,8]. According to the theory of penecontemporaneous replacement, early diagenetic dolomitization of calcite or aragonite precursors occurred at temperatures of <60 °C via Mg-rich reflux in pore water [9].…”
Section: Introductionmentioning
confidence: 99%